Morphological characteristics, dry matter yield, and nutritive value of maralfalfa grass (Pennisetum spp.) grown under different planting densities in the central highlands of Ethiopia - Mengistu, Gezahegn; Kebede, Gezahagn; Faji, Mulisa; Feyissa, Fekede; Mohammed, Kedir; Kehaliew, Aemiro; Geleti, Diriba; Minta, Muluneh; Balehegn, Mulubrhan; Rios, Estebah F.; Adesogan, Adegbola T.; Dubeux, Jose C. B.; et al. (Frontiers in Animal Science, 2024)
Maralfalfa grass (Pennisetum spp.) is known for its high dry matter productivity and nutritive value. However, information on agronomic management practices to improve yield and nutritive value in Ethiopia is sparse. Thus, the effects of plant density on morphological characters, dry matter production, and nutritive value of Maralfalfa grass were evaluated during the 2019 and 2020 cropping seasons at Holetta, in the central highland of Ethiopia. The experiment consisted of 7 plant densities (33,333 [75 cm x 40 cm]; 26,667[75 cm x 50 cm]; 25,000 [100 cm x 40 cm]; 22,222 [75 cm x 60 cm]; 20,000 [100 cm x 50 cm]; 16,667 [100 cm x 60 cm]; and 13,333 [125 cm x 60 cm] plants per hectare, and arranged in randomized complete block design with three replications. The results indicated that the year had a significant (P<0.001) effect on measured traits. Plant densities had no significant (P>0.05) effect on the number of nodes and leaves per plant, leaf length, and basal diameters. The number of tillers per plant varied significantly among plant densities only in the first year at the 1st harvest. Plant height in the first year was significantly (P<0.01) greater than in the second year. Annual dry matter production and annual crude protein production of Maralfalfa grass were not significantly affected by plant density. Nutritive value parameters (CP, Ash, NDF, ADF, ADL, and IVDMD) were not significantly (P > 0.05) influenced by plant density. Using a lower plant density could reduce the amount of planting material, transport, and labor costs. Hence, using a wider spacing of 125 x 60 cm (13333 population ha-1) can be an appropriate planting density for optimum dry matter production in the study area and similar agro-ecologies of the country. However, However, further studies on Maralfalfa grass should be conducted in multi-locations of Ethiopia both under rain-fed and irrigated conditions with various agronomic practices.